Analysis of motor performance of professional soccer players in different environmental conditions - Konefał, Marek; Chmura, Paweł; Andrzejewski, Marcin; Chmura, Jan (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Air temperature and humidity affect the motor activity of soccer players during matches. Analysis of soccer players’ motor activity in extreme environmental conditions enables optimal players’ preparation. Aim of Study. The study aims to assess changes in motor performance of soccer players in different environmental conditions. Material and Methods. The participants were soccer players taking part in the 2014 World Cup matches in Brazil. The authors used the Castrol Performance Index motion analysis system for data recording. Results. Higher air temperature reduces the performance of exercise with medium (p ≤ 0.05) and high intensity (p ≤ 0.01); while higher humidity has a significant positive impact on the distance covered by players with medium intensity (p ≤ 0.05). The total number of performed sprints becomes significantly lower in higher air temperature and humidity (p ≤ 0,05). Conclusions. Soccer training should emphasize highintensity exercise as well as short-lasting and explosive exercise since the environmental conditions have a greater impact on players’ speed skills than endurance skills
Keywords: soccer; World Cup; professional soccer players; temperature; humidity; endurance; speed